A Note on the Cause of the Nuisance of Barking at Night on New Providence, The Bahamas - Fielding, William J. (International Journal of Bahamian Studies, 2008)
Barking dogs, both roaming and unowned, are regarded as a nuisance throughout New Providence. With most dogs being owned for protection, either as watch or guard dogs, it is apparent that many people keep dogs specifically to bark. This observational study of 551 dogs, in 14 areas of greater Nassau, showed that confined, barking dogs constituted the single largest group of dogs (37.4%) observed at night. A smaller percentage of unconfined (48.0) the confined dogs (68.5%) barked at night. Almost half (45.5%) of the roamers observed were unconfined. The study indicated that confined dogs constitute the majority of barking dogs and so are the major causes of the nuisance of barking at night.